A cyclic visco-plastic constitutive model for the ratcheting behavior of U75VG rail steel under a wide range of loading rates. (August 2022) - Zhao, Jizhong; Fu, Peilin; Xu, Xiang; Zhang, Xu; Wang, Ping; Kan, Qianhua
Highlights: Rate-dependent experiments of U75VG rail steel were carried out. A new cyclic visco-plastic constitutive model was established. Rate-dependent ratcheting behaviors of U75VG rail steel were simulated. Factors influencing the rate effect were discussed. Abstract: The uniaxial tension, strain-controlled and stress-controlled cyclic deformation experiments of U75VG rail steel at various loading rates were carried out. Experimental results show that the U75VG rail steel shows obvious rate-dependent tension, cyclic softening feature and ratcheting behavior. Moreover, based on the rate-dependent experimental results, a new cyclic visco-plastic constitutive model was established by introducing the rate-dependent isotopic resistance and ratcheting factor into isotropic and kinematic hardening rules, respectively. Compared with the classic cyclic visco-plastic model, the proposed model can reasonably simulate the tension, strain-controlled and stress-controlled cyclic deformation behaviors at different loading rates. Finally, the prediction capacity of ratcheting behavior under a wide range of loading rates was demonstrated.